The McKusick-Kaufman syndrome: report of a case with some associations - (:unkn) unknown (TURKISH J PEDIATRICS, 2002)
McKusick-Kaufman syndrome (MKS) is a rare autosomal recessive condition consisting of congenital hydrometrocolpos, polydactyly and congenital heart defect. We present a female stillborn, the product of non-consanguineous parents, who presented postaxial polydactyly on both feet, micrognathia and marked abdominal distension. Postmortem examination revealed bicornuated cystic uterus and intestinal malrotation. She also had flat left kidney and left hydroureter due to compression by the cystic mass.
Keywords: congenital hydrometrocolpos; bicornuated uterus; polydactyly; vaginal atresia; hydroureter; malrotation; abdominal cyst; ABDOMINAL DISTENSION; HYDROMETROCOLPOS